Sosialisasi Penggunaan Sosial Media Yang Baik Dalam Menanggulangi Berita Hoax Di Yayasan Pondok Kasih Surabaya - Rezy Garda Suraya; Ahmad Kayyis; Roby Firmansyah; Aprilia Muchyidini; Giffary Bagas; Athok Murtadhlo (Prapanca : Jurnal Abdimas, 2022)
Pondok Kasih Foundation is a home where people who are rejected by the community can feel God's acceptance of God. On the basis of people with various needs, one of them serves children with a variety of different backgrounds. With the lack of supervision of his parents, one of them when using a gadget without more assistance than parents. Children become out of control so that anything can be accessed freely without knowing whether or not it is. The purpose of this Field Work Lecture is to help them so they can access the internet according to their age and can sort out which are good and which are bad. and we use the method of observation and interviews with related parties at the Pondok Kasih Foundation regarding this socialization. Praise the results we received from the Foundation good and positive, hopefully it can provide benefits for the Foundation because of this socialization